NUTRIENT DIGESTIBILITY FEED WITH DIFFERENT LEVELS OF PROTEIN AND LIPID ON CORAL ROCK GROUPER (Epinephelus corallicola) JUVENILE - Muhammad Marzuqi; Dewi Nasbha Anjusary (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The aims of this study was to determine the nutrient digestibility coefficient of diet with diertary levels of protein and lipid on coral rock grouper (Epinephelus corallicola) juvenile. This study used completely randomized design with factorial arranged in 3 different treatment of dietary protein levels i.e., 36%, 42%, and 48%;and 2 different treatment of dietary lipid levels i.e., 9% and 18%; with 3 repetition. The average initial body weight of fishes for this study was 29.19 ± 0.97 g/fish. Fishes were reared in 18 pieces of polycarbonate tank with water volume of 30 liters with stocked density of 7 fishes/tank. The tank equipped with aeration with water flow change of 20 liters/hour. Fish were fed 2 times per day on at satiation and fish rearing for 150 days. Parameters measured were protein, lipid, carbohydrate and energy of digestibility coefficient . The results showed that the interaction of protein and lipid levels that differ in feed ratio significantly affected on protein, lipid, carbohydrate, and energy digestibility coefficients. In general, feed with a protein content of 36% and 9% lipid produced good nutrient digestibility coefficient and better economic value. Keywords: protein, lipid, feed nutrient digestibility, coral rock grouper